Springtails (Collembola) in meadows, pastures and road verges in Central Finland - Komonen, Atte; Kataja-aho, Saana (Entomologica Fennica, 2017)
Understanding of species distribution, abundance and habitat affinities is crucial for red-list assessment, conservation and habitat management. In Central Finland, we studied Collembola in three habitat types, namely non-grazedmeadows, pastures and road verges using pitfall traps. Altogether, 9,630 Collembola individuals were recorded. These belonged to 12 families, 34 genera and 60 species. The number of specimens was clearly higher in meadows than in pastures or road verges. The number of species, however, was higher in meadows and road verges (40 and 39 species, respectively) than in pastures (33 species). The overall species number is comparable to other large-scale sampling schemes in similar habitats. We recorded a few abundant species (Spatulosminthurus flaviceps, Sminthurus viridis and Sminthurus nigromaculatus) that have been previously recorded from very different biotopes. In conclusion, biodiversity inventories of soil fauna, as well as other biota, should also include marginal habitats, which often host peculiar communities.